Pulsed Radiofrequency: A Review of the Basic Science as Applied to the Pathophysiology of Radicular Pain. Issue 2 (1st March 2014) - Van Boxem, Koen; Huntoon, Marc; Van Zundert, Jan; Patijn, Jacob; van Kleef, Maarten; Joosten, Elbert A.
Abstract : Abstract: Radicular pain is an important health care problem, with only limited evidence-based treatments available. Treatment selection should ideally target documented pathophysiological pathways. In herniated discs, a sequence in the inflammatory cascade can be observed that initiates and maintains increased nociceptive signal input. Inflammatory mediators including tumor necrosis factor α are released from the nucleus pulposus and the degenerating peripheral nerve, which, in turn, induces production of neurotrophins like nerve growth factor and brain-derived neurotrophic factor. Neurotrophins interfere not only with the generation of ectopic firing of nociceptive neurons in the dorsal root ganglion but also with the excitability and sensitization of neuronal transmission in the dorsal spinal horn. Radicular pain is further characterized by the electrophysiological spreading of the afferent nociceptive input over different spinal nerve roots. Both the complex pathophysiological pathways involved and the spreading of the nociceptive signal make radicular pain difficult to treat. Pulsed radiofrequency (PRF) is considered an option in treatment of radicular pain. To understand and increase the efficiency of PRF interventional treatments in radicular pain, both in vitro and in vivo studies aiming at elucidating part of the mechanism of action of PRF are described. Potential factors that may improve the efficacy of PRF treatment in radicular pain are discussed.